Breakfast Type and Cardiovascular Mortality: The Japan Collaborative Cohort Study - Jingyun Tang; Jia-Yi Dong; Ehab S. Eshak; Renzhe Cui; Kokoro Shirai; Keyang Liu; Akiko Tamakoshi; Hiroyasu Iso; the JACC study group (Journal of Atherosclerosis and Thrombosis, 2023)
Aim: Little is known regarding the association between breakfast type and cardiovascular mortality. We examined the associations between breakfast type and risks of mortality from stroke, coronary heart disease (CHD), and total cardiovascular disease (CVD). Methods: A total of 85,319 males and females aged 40 to 79 years who were free from CVD and cancers at baseline were involved in this study. The participants were divided into five groups according to their selfreported breakfast types: Japanese breakfast, Western breakfast, mixed Japanese-Western breakfast, other breakfast, and skipping breakfast groups. All hazard ratios (HRs) were estimated using Cox proportional hazards regression models after adjusting for the potential confounding factors. Results: During the median 19-year follow-up, we identified CVD deaths of 5,870 subjects. Compared to the Japanese breakfast, the multivariable HRs (95% CIs) of total CVD were 0.64 (0.52-0.79) for mixed Japanese- Western breakfast, 0.90 (0.77-1.04) for Western breakfast, 1.24 (0.95-1.61) for other breakfast, and 1.31 (1.00-1.71) for skipping breakfast. The corresponding HRs (95% CIs) of total stroke were 0.67 (0.49-0.91), 0.83 (0.66-1.05), 1.15 (0.76-1.74), and 1.25 (0.82-1.92), and those of CHD were 0.73 (0.48-1.12), 1.08 (0.81-1.44), 1.09 (0.60-1.98), and 1.77 (1.11-2.83). Conclusion: Compared to Japanese breakfast, mixed Japanese-Western breakfast may have a protective role in cardiovascular mortality whereas skipping breakfast may harm cardiovascular health.